AVALIAÇÃO DA QUALIDADE DA ÁGUA EM NASCENTES DO MUNICÍPIO DE PRUDENTÓPOLIS - PR - ANTONIO, LUCIANO MARCOS (2023)
The disorderly growth of cities strongly contributes to the degradation of water resources, compromising water quality and the integrity of these environments. The decrease in the level and variation of rainfall, the waste of water, the increase in consumption due to population, industrial and agricultural growth, the contamination of water reservoirs can degrade the entire ecosystem. Springs have an important environmental role because, in addition to providing water for streams and rivers that supply society, they are also a source of life for other organisms. The preservation of water sources is a measure adopted to avoid damage caused by man, ensuring that everyone continues to have access to this resource that is so important, both for the survival of human beings and for plants and animals. The objective of this study was to evaluate whether the recovery method of springs in the municipality of Prudentópolis is being efficient through the evaluation of some parameters. Eight different scenarios were used. In four, the recovery was in the soil-cement system. Eight springs were identified in the municipality of Prudentópolis in different types of land use, namely: agriculture, farms with extensive animal husbandry, forest and urban area. In each type of land use, samples were collected from two springs, one recovered by the soil-cement system and the other without recovery. Two campaigns were carried out at each source. The parameters used to evaluate the water quality of the springs were: turbidity, pH, phosphorus, alkalinity, total coliforms and Escherichia coli. In the springs where the recovery occurred, analyzing the recovery method itself, there was less turbidity, the pH was higher, and the values of total coliforms and E.coli were lower. When comparing data from the same type of land use, it is observed that this recovery method is not efficient; in the case of agriculture, phosphorus was found in similar concentration in samples from recovered and non-recovered springs. In the forest area, the difference between the recovered and non-recovered springs in the E. coli and turbidity parameters is evident in at least three times the values, being favorable for the recovered ones. In the case of springs located in faxinais, the data indicated better water quality in all variables. But the presence of E. coli at fifteen times higher in the non-recovered spring compared to the recovered one is mainly due to animal contact. In both cases the water was unfit for consumption.